2022
DOI: 10.1101/2022.04.21.489109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The kinase activity of the cancer stem cell marker DCLK1 drives gastric cancer progression by reprogramming the stromal tumor landscape

Abstract: Gastric cancer (GC) is the 3rd leading cause of cancer mortality worldwide, therefore providing novel diagnostic and treatment options is crucial for at risk groups. The serine/threonine kinase doublecortin-like kinase 1 (DCLK1) is a proposed driver of GC with frequent amplification and somatic missense mutations yet the molecular mechanism how DCLK1 mediates tumorigenesis is poorly understood. We report how DCLK1 expression orchestrates complementary cancer cell intrinsic and extrinsic processes leading to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Many studies have shown that the overexpression of DCLK1 in cancer cells results in induction of EMT, stemness and increased cell migration and invasion, which can be reversed with small molecules targeting the kinase domain of DCLK1 [ 31 , 34 , 35 , 46 , 47 , 126 ]. In addition, targeting DCLK1 with anti-DCLK1 monoclonal antibody (CBT-15) or siRNAs showed promising results in reducing tumor burden, cancer stemness, invasion, and metastasis [ 31 , 35 , 41 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ]. It remains to be shown whether such anti-DCLK1 targeting approaches are equally effective in the context of the various DCLK1 missense mutations that promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the overexpression of DCLK1 in cancer cells results in induction of EMT, stemness and increased cell migration and invasion, which can be reversed with small molecules targeting the kinase domain of DCLK1 [ 31 , 34 , 35 , 46 , 47 , 126 ]. In addition, targeting DCLK1 with anti-DCLK1 monoclonal antibody (CBT-15) or siRNAs showed promising results in reducing tumor burden, cancer stemness, invasion, and metastasis [ 31 , 35 , 41 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ]. It remains to be shown whether such anti-DCLK1 targeting approaches are equally effective in the context of the various DCLK1 missense mutations that promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%